MODELAGEM DE PROCESSOS PARA MELHORIA EM UNIDADES DE INFORMAÇÃO: O CASO DO CEFET/RJ - Rosa, Samantha Andrade da (2013)
In organizations, whether with or nonprofit management is critical to the development of their competitive advantage. The identification and understanding of the processes carried out by these is currently one of the most important skills, especially when the products resulting from these processes are intangibles, such as libraries. The objective of the research is to identify if there inefficiency in the technical processing of the CEFET / RJ libraries. The literature review presents the main concepts about the management of business processes and their application in libraries. The methodology adopted in this research is about the purposes of exploratory and applied as to the means and research strategies used will be the literature review and case study that will be held in the libraries defined as a sample , using interviews to survey the processes. The standard model will be adopted BPMN (Business Process Modelling Notation). The research aims to contribute to the areas of Production Engineering and librarianship to address, respectively, the management of business and library management from a new perspective process issues. The modeling performed suggested the critical points of technical processing, which have been proposed improvements. The technique was feasible for assessing processes in libraries